2021 Comprehensive Surveillance Review : Background Paper on The Surveillance Priority Confronting Risks and Uncertainties. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2021)
The coverage of risks has become more systematic since the Global Financial Crisis (GFC): staff reports now regularly identify major risks and provide an assessment of their likelihood and economic impact, summarized in Risk Assessment Matrices (RAM). But still limited attention is paid to the range of possible outcomes. Also, risk identification is useful only so much as to inform policy design to preemptively respond to relevant risks and/or better prepare for them. In this regard, policy recommendations in surveillance could be richer in considering various risk management approaches. To this end, progress is needed on two dimensions: -- Increasing emphasis on the range of potential outcomes to improve policy design. -- Encouraging more proactive policy advice on how to manage risks. Efforts should continue to leverage internal and external resources to support risk analysis and advice in surveillance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Financial Crises; Monetary Policy; Political Economy